A cross-sectional study of anxiety and depression caseness in female competitive figure skaters in Sweden. Issue 1 (8th March 2023) - Jederström, Moa; Agnafors, Sara; Ekegren, Christina L; Fagher, Kristina; Gauffin, Håkan; Korhonen, Laura; Park, Jennifer; Spreco, Armin; Timpka, Toomas
Abstract : Objectives: Little is known about figure skaters' mental health. This study aimed to describe anxiety and depression caseness (defined as a screening condition qualifying for psychiatric examination) in competitive figure skaters and analyse factors associated with such caseness. Methods: A cross-sectional study was performed in April 2019 among all competitive figure skaters in the south-eastern region of Sweden (N=400). The primary outcomes were anxiety caseness, measured using the short-form Spielberger State-Trait Anxiety Inventory and depression caseness, measured using the WHO-5 index. Multivariable logistic regression models were employed to determine the association between anxiety caseness and explanatory factors. Results: In total, 36% (n=142) of the invited skaters participated. Only females (n=137), mean age 12.9 (SD 3.0) years) were selected for analysis. Of the participating skaters, 47% displayed anxiety caseness and 10% depression caseness. Overweight body image perception (OR 5.9; 95% CI 2.0 to 17.6; p=0.001) and older age (OR 1.2; 95% CI 1.1 to 1.4; p=0.005) were associated with anxiety caseness. Skaters reporting no caseness were younger than those reporting only anxiety caseness (mean age difference −1.9 years; 95% CI −3.1 to −0.7; p=0.001) or anxiety and depression caseness (OR −3.5 years; 95% CI −5.6 to −1.5 years; p<0.001). Conclusion: Anxiety caseness was associated with overweight body image perception and older age in female competitive figure skaters. Older skaters reported generally worse mental health. More research on the mental health of figure skaters is warranted, considering comorbidity and focusing on those needing further assessment and support.